A multi-group structural equation modelling analysis for the impact of digital art on critical thinking across language contexts - Gulvira Togabayeva; Rabilova Zoya; Miyat Janayev; Gulnar Shaizadanova; Anarbek Kozybay (Institute of Advanced Engineering and Science, 2026)
This study investigates the structural relationships among creativity (Crtvt), technological adaptability (TchAd), problem solving (PrblS), analytical thinking (Anlyt), and self-reflection (SlfRf) in the context of digital art education. A total of 249 students from three higher education institutions in Kazakhstan participated in the study. Using a 25-item Likert-scale instrument, data were collected from students instructed in either Kazakh or Russian. Structural equation modeling (SEM) with multi-group analysis was employed to test a theoretically grounded model of critical thinking development through digital art. The results revealed that Crtvt and TchAd significantly predicted students’ problem-solving abilities, which in turn emerged as the strongest predictor of both Anlyt and SlfRf. Crtvt also had moderate direct effects on these higher-order thinking outcomes, while TchAd showed a stronger influence on PrblS and SlfRf than on Anlyt. Multi-group analysis indicated that the measurement and structural models were invariant across language groups.